A Systematic review comparing outcomes of laparoscopic and transvesicoscopic ureteroneocystostomy (Herald of the National Children's Medical Center, 2025)
Background. We have examined and compared the results of the articles on LEVUR and TVUR in this systematic review and meta-analysis.Materials and methods. To find all the studies about TVUR and LEVUR in the pediatric population, we examined the databases. Exclusions were review articles, unfinished articles, duplicate publica- tions, and robot-assisted publications. To determine patient information, reflux grades, laterality, length of operation, time to discharge, success rate, and complications, a systematic review was carried out.Results. 23 articles -13 on TVUR and 10 on LEVUR - were included after a total of 45 articles were screened. In TVUR grade 5 VUR was substantially larger (11.9%, p = 0.001) than in LEVUR (2.2%). When comparing TVUR to LEVUR, the percentage of bilateral reimplantation was considerably higher (p = 0.001). 96.7% was the success rate of LEVUR, a considerable increase above TVUR 93.7% (p = 0.007). Unilateral/bilateral TVUR took significantly longer duration of surgery (155/194 min vs 107/161 min) compared to LEVUR (p = 0.001). The mean (s.d) time to discharge was longer at 3.2 (1.6) days for TVUR compared to 1.6 (0.4) days for LEVUR (p = 0.001). The complication rate was comparable, 7.35% for TVUR and 5.35% for LEVUR (p = 0.167).Conclusion. With regard to success rates and side effects, LEVUR and TVUR appear to be reason- able substitutes for open ureteric reimplantation. Compared to TVUR, which was recommended for bilateral UR and grade 5 VUR patients, LEVUR was more preferable for unilateral, grades 1-4 cases, had higher success, and required a shorter hospital stay. Although the types of complications varied according to the procedure, there was no discernible difference in the complication rate between LEVUR and TVUR.
Keywords: vesico-ureteral reflux; ureteral reimplantation; systematic review; laparoscopic surgery; transvesicoscopic surgery